Indigenous Persistence in the Colonized Americas : Material and Documentary Perspectives on Entanglement - Sheptak, Russell N., 1955-; Law Pezzarossi, Heather, 1979- (Book collections on Project MUSE., 2019)
This scholarly collection explores the method and theory of the archaeological study of indigenous persistence and long-term colonial entanglement.